Blood biomarkers of secondary outcomes following concussion: A systematic review - Swaney, Ella E. K.; Cai, Tengyi; Seal, Marc L.; Ignjatovic, Vera (Frontiers in Neurology, 2023)
Introduction Blood biomarkers have been identified as an alternative tool for predicting secondary outcomes following concussion. This systematic review aimed to summarize the literature on blood biomarkers of secondary outcomes following concussion in both pediatric and adult cohorts. Methods A literature search of Embase, Medline and PubMed was conducted. Two reviewers independently assessed retrieved studies to determine inclusion in systematic review synthesis. Results A total of 1771 unique studies were retrieved, 58 of which were included in the final synthesis. S100B, GFAP and tau were identified as being associated with secondary outcomes following concussion. Seventeen percent of studies were performed in a solely pediatric setting. Conclusions Validation of biomarkers associated with secondary outcomes following concussion have been largely limited by heterogeneous study cohorts and definitions of concussion and mTBI, presenting a hurdle for translation of these markers into clinical practice. Additionally, there was an underrepresentation of studies which investigated pediatric cohorts. Adult markers are not appropriate for children, therefore pediatric specific markers of secondary outcomes following concussion present the biggest gap in this field.